Asset Management for Infrastructure Systems Energy and Water - Balzer, Gerd.; Schorn, Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The book offers a broad overview of asset management processes for different utilities, with a special emphasis on energy and water. It provides readers with important practical considerations concerning the development of new competitive structures and procedures for guaranteeing a sufficient supply of energy and water in a regulated environment, using clearly defined technical and economic cornerstones. On the one hand asset owners expect suitable interests from their investment and business growth; on the other hand regulators focus more on a reliable and cost-effective customer supply. This book shows how to take into consideration these different perspectives in the process of designing new structures, and how to guarantee organizational transparency. Based on the major tasks of an asset manager, it describes essential principles and boundary conditions for ensuring the optimal use of resources in a network, such as investment and maintenance strategies, equipment service life, investment and operational costs, etc. Moreover, it points out their impact on the organization of the company, including the necessary IT landscape and computer programs. The book is the English translation of Asset Management für Infrastrukturanlagen - Energie und Wasser1, written by the same authors and published by Springer in 2014.
Introduction -- Tasks of the Asset Management -- Control functions -- Integration into the Business Organization -- System Landscape in the Area of Asset Management.
Keywords: Energy; Energy policy; Energy and state; Environmental management; Management information systems; Computer science; Facility management; Energy; Energy Policy, Economics and Management; Water Policy/Water Governance/Water Management; Facility Management; Management of Computing and Information Systems; Electronic books